Interpolations in the Pauline Letters. - Walker, William (Library of New Testament studies., 2002)
In this fundamental and at times provocative study, Walker demonstrates that Paul's letters contain later, non-Pauline additions or interpolations and that such interpolations can sometimes be identified with relative confidence. He begins by establishing that interpolations are to be assumed simply on a priori grounds, that direct text-critical evidence is not essential for their recognition, that the burden of proof in their identification is lighter than most have assumed, and that specific evidence for interpolation is often available. Successive chapters then argue that 1 Cor. 11.3-16, 1 C.